Influence of aggregate absorption and diffusion properties on moisture damage in asphalt mixtures - Apeagyei, Alex K.; Grenfell, James R.A.; Airey, Gordon (Taylor & Francis, 2015)
An experimental study was undertaken to characterise moisture sensitivity of asphalt mixtures by comparing certain physico-chemical properties of selected aggregates of different mineralogies to the moisture induced strength degradation of the aggregate–mastic bonds. The aim of the study was to evaluate the effect of using different aggregate types (as substrates) with a single mastic type that had shown severe moisture sensitivity in the past when combined with a susceptible aggregate substrate. Four different aggregate types and an asphalt mastic (made with a 40/60 pen base bitumen) were used. Aggregate moisture sorption at ambient temperature was characterised using gravimetric techniques. Aggregate specific surface area was determined by octane adsorption using a dynamic vapour sorption device. Dynamic mechanical analysis techniques based on data from a dynamic shear rheometer were used to characterise the rheological properties of the asphalt mastic. Aggregate–mastic bond strength as a function of moisture conditioning time was determined using a tensile pull-off test set-up. The results were used to estimate equilibrium moisture uptake, diffusion coefficient, characteristic diffusion time, and aggregate ‘porosity’. The effect of moisture on bond strength was aggregate substrate-type-dependent with three out of the four aggregates performing well and the fourth performing poorly. The moisture absorption and diffusion properties of the poorly performing aggregates were worse than the ‘good’ performing aggregates. Susceptible aggregate–mastic bonds had high porosity, high moisture absorption, high diffusion coefficient and contained granite as substrates. Results of statistical analyses suggested that the differences in moisture sensitivity of the other three aggregates were not significant. Therefore, two unique damage models, one for ‘good’ performing and another for ‘poor’ performing were proposed to characterise moisture damage sensitivity of asphalt. The influence of aggregate moisture absorption and diffusion on asphalt mixture moisture damage was found to be aggregate-type-dependent. The results also suggested that in a susceptible mixture, the effect of the substrate aggregate may be more influential than the effect of mastic. The results have important implications for the selection of coarse aggregate for asphalt mix design.